A multicenter randomized controlled clinical pilot study of buccally micro‐veneered lithium‐disilicate and zirconia crowns supported by titanium base abutments: 1‐year outcomes. Issue 1 (13th November 2022) - Strasding, Malin; Hicklin, Stefan Paul; Todorovic, Ana; Fehmer, Vincent; Mojon, Philippe; Sailer, Irena
Abstract: Objectives: To investigate survival rates, technical and biologic outcomes of buccally micro‐veneered all‐ceramic single implant crowns. Material and Methods: Sixty subjects randomly received immediately or early placed implants. Crowns out of lithium‐disilicate ( n = 30) and zirconia‐ceramic ( n = 30) were bonded to titanium‐base‐abutments. Restorations were inspected at baseline (BL) and during follow‐up visits (6, 12 months). Technical and biologic parameters were recorded. Data were analysed descriptively. Differences between groups were tested with Student's t ‐test. Paired T‐test was used when comparing data from the same implant or tooth over time. Linear model repeated measures were used to test differences between materials over time. Differences in counts were evaluated using Pearson Chi‐square test. The level of significance was at p < .05. Results: After a mean observation time of 13.2 ± 2.4 months, 54 restorations were re‐examined. The implant survival rate was 98.3%, and the restoration survival rate was 100%. One early implant failure occurred. Two minor chippings occurred in lithium‐disilicate restorations. No chippings or fractures occurred in any zirconia restorations at 1 year (0%). The technical complication rate was 3.7%, with 7.7% complications among the lithium‐disilicate restorations and no differences between the two materials ( p = .558). At 1‐year follow‐up, mean Bleeding on Probing (BOP) was higher at implants (0.27 ± 0.3) than adjacent teeth (0.17 ± 0.18) ( p = .046) with no differences between materials ( p = .36). Differences in pocket probing depth (PPD) between implants and adjacent teeth were significant ( p < .01). Jemt Index improved significantly from BL to 1‐y‐follow‐up ( p < .001). Conclusions: Preliminary results were good, suggesting that the ceramic type does not impact technical and biologic parameters.